(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The severety of outcomes of eye contusion are of current interest, so it is very important to study structural changes and possibilities of their correctionin experiments. Purpose. To create the device for experimental modeling of eye contusion of various severity in different animals. Material and methods. There is the device with kits of springs, missile projectiles with different mass and form. Eye contusion in animals is modeled by this device with springs, missile projectiles orpeen. Results. The device with missile and impact mechanisms is found. It allows to model eye contusion of various severity through open eyelids in rabbits and rats. Conclusion. This device allows to model standart eye contusion of various severity in animals with different eye sizes (rabbits, rats), to perform dynamic analysis of impact action, to calculate area-normalized kinetic energy.